Pendampingan Penyusunan Rencana Induk Kawasan Asrama Haji Embarkasi Banjarmasin Sebagai Upaya Pemenuhan Standar Kawasan - Caesarina, Hanny Maria; Djaenudin, Achmad Zabir; Aziz, Abdul (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2024)
The Banjarmasin Embarkation Hajj Dormitory is currently trying to improve its service quality for prospective Hajj pilgrims. At the moment, the area which were built in 1980, no longer meets state building planning standards which might have an impact on decreasing service quality. Outside the Hajj season, the dormitory can also be used by the community, government agencies and socio-religious organizations for activities. This community service activity aims to analyse the suitability of the area as a type E.1 Hajj dormitory area so that it can meet national standards as the basic framework for masterplan through 4 series of group discussion forum. From total of 14 buildings, 4 still meet national standards set by the Indonesian Ministry of Religion, the Director General of Hajj and Umrah. Hence, to revitalize the area, several changes are needed such as developing vehicle and pedestrian circulation routes, building new dormitories, polyclinics, airplane mock-up studios, developing utility networks and clean water , as well as moving the Hajj ritual area. The final evaluation shows results that 4 out of total 14 standards were only maximum 80% developed due to the limited site. However, the master plan reaches 100% for the rest 10 standards.